Age-Specific Imbalance of Circulating Tfh Cell Subsets and Its Association With Gout-Targeted Kidney Impairment - Huang, Yefei; Wu, Xinyu; Gui, Lian; Jiang, Yutong; Tu, Liudan; Li, Xiaomin; Jiang, Boxiong; Wang, Yina; Zheng, Xuqi; Wei, Qiujing; Li, Qiuxia; Ou, Jiayong; et al. (Frontiers in Immunology, 2021)
Objective: Gout is a chronic disease characterized by the deposition of monosodium urate (MSU) crystals in tissue. The regarding study with a focus of adaptive immune response remain to be fathomed, while innate immune response has been reported extensively in gout etiology. Our study attempted to interrogate the associations of gout-related immune cells imbalance with clinical features and the comorbidity with renal impairment and the implicated pathogenesis via the assessment of T and B cell subsets in different activity phases or with immune effects combined with the analyses of clinical parameters. Methods: 58 gout patients and 56 age- and sex- matched healthy individuals were in the enrollment. To unfold the roles of circulating T cells, a lymphocyte profile incorporating with 32 T cell subsets was tested from the isolated freshly peripheral blood monocyte cells (PBMCs) with multiple-color flow cytometry. Furthermore, collected clinical features of participants were used to analyze the characteristics of these differential cell subsets. Stratified on the basis of the level of creatinine(Cr, enzymatic method), all patients were categorized into Crlow(Cr ≤116 μmol/L) group and Crhi group (Cr>116 μmol/L), thus to exploit whether these gout-associated T cell subsets were functional in the gout-targeted kidney dysfunction. Mechanismly, the differentiation of B cells was investigated in gout patients. Results: Our results showed that CD 4+ T cells, Th2 cells and Tc2 cells were upregulated, whereas Tc17 cells were downregulated. Tfh cells skewed toward the polarization of Tfh2 cells. Specifically, Tfh2 cells increased but Tfh1 cells decreased accompanied with aging for gout patients, suggesting that age might trigger the skewing of Tfh1/Tfh2 cell subsets to influence gout development. Moreover, Tfh2 cells argument was connected to renal dysfunction as well. No alterations of B cell subsets were observed in patients when compared to controls. Conclusions: Our date demonstrated age-specific dysfunctions of Tfh1/2 cells in gout occurrence, and Tfh2 cells upregulation is associated with gout-targeted renal dysfunction. However, Tfh2 cells may function in the auto-inflammatory gout independent on helping B differentiation, and the in-depth study remain be conducted.